2014
DOI: 10.1080/09571736.2014.891396
|View full text |Cite
|
Sign up to set email alerts
|

Issues in the assessment of bilingually educated students: expressing subject knowledge through L1 and L2

Abstract: This article discusses issues related to oral assessment of school knowledge of L2-educated students. In particular, it examines benefits and disadvantages of students being tested in their L1 (their dominant language) and in their L2 (their language of instruction). The study draws on the data from 37 high school students studying in a content and language integrated learning (CLIL) setting in Slovakia. They were tested both in their L1 (Slovak) and their L2 (English) on material which they read in English. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 22 publications
(25 reference statements)
1
3
0
Order By: Relevance
“…They perceived this as a more effective approach to access content (see also [31]). Similar findings can be seen in the United Arab Emirates [32], Thailand [33], and Slovakia [34], where it was found that English may constrain students' ability to express the knowledge that they have in their L1 (see also [21,35]).…”
Section: Comparing Emi and L1 Students' Academic Resultssupporting
confidence: 80%
“…They perceived this as a more effective approach to access content (see also [31]). Similar findings can be seen in the United Arab Emirates [32], Thailand [33], and Slovakia [34], where it was found that English may constrain students' ability to express the knowledge that they have in their L1 (see also [21,35]).…”
Section: Comparing Emi and L1 Students' Academic Resultssupporting
confidence: 80%
“…Zafiri and Zouganeli, 2017). I S S N : 1 9 8 8 -8430 Gablasova (2014) studied two groups of Slovak students from the same bilingual high school, the same contents were presented in their L1 (Slovak) to one of the groups and in their L2 (English) to the other. Her findings show certain constraints in bilingually educated students' L1 performance, as compared to those who receive instruction only in their L1, more specifically disfluencies and the use of inaccurate terms were observed in the L2-educated group.…”
Section: L1 In the Assessment Processmentioning
confidence: 99%
“…knowing facts and figures. Examples for these studies would be Badertscher and Bieri (2009), Gablasova (2014) or Dallinger et al (2016), which all suggest that attaining factual knowledge via an L2 is indeed (satisfactorily) possible, but the actual learning effect has yet to be determined. Looking at current European history curricula, declarative knowledge, however, does not seem to be the prime learning goal any longer (Heil, 2012;van Drie & van Boxtel, 2008).…”
Section: Integration Of Subject-specific and Language-didactic Perspementioning
confidence: 99%